1990
DOI: 10.1148/radiology.176.2.2367658
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR imaging of anisotropic water diffusion in cat central nervous system.

Abstract: The diffusion behavior of intracranial water in the cat brain and spine was examined with the use of diffusion-weighted magnetic resonance (MR) imaging, in which the direction of the diffusion-sensitizing gradient was varied between the x, y, and z axes of the magnet. At very high diffusion-sensitizing gradient strengths, no clear evidence of anisotropic water diffusion was found in either cortical or subcortical (basal ganglia) gray matter. Signal intensities clearly dependent on orientation were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
566
1
15

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,020 publications
(592 citation statements)
references
References 0 publications
10
566
1
15
Order By: Relevance
“…1(A)] and that the orientation of the largest principal axis aligns to the predominant axonal orientation. 3,[44][45][46][47] However, when studying axonal architecture using DTI, it is very important to understand the limitations arising from the inhomogeneity of the water environment. First, the conventional DTI data acquisition and processing methods may not be able to properly handle a voxel containing more than one population of axonal tracts with different orientations.…”
Section: Cellular Architecture Superimposes Orientation On the Randommentioning
confidence: 99%
See 1 more Smart Citation
“…1(A)] and that the orientation of the largest principal axis aligns to the predominant axonal orientation. 3,[44][45][46][47] However, when studying axonal architecture using DTI, it is very important to understand the limitations arising from the inhomogeneity of the water environment. First, the conventional DTI data acquisition and processing methods may not be able to properly handle a voxel containing more than one population of axonal tracts with different orientations.…”
Section: Cellular Architecture Superimposes Orientation On the Randommentioning
confidence: 99%
“…3 In the last decade, the quantitative description of this anisotropy with diffusion tensor imaging (DTI) has become well established in the research environment and its first applications in the clinic are now being reported. These applications employ both the directional anisotropy that can be measured by DTI 4,5 as well as removal of this anisotropy through the use of the tensor trace.…”
Section: Introductionmentioning
confidence: 99%
“…isotropic), it is usually sufficient to characterize the diffusion characteristics with a single (scalar) apparent diffusion coefficient (ADC). However, in anisotropic media, such as skeletal and cardiac muscle [6][7][8] and in white matter, [9][10][11] where the measured diffusivity is known to depend upon the orientation of the tissue, no single ADC can characterize the orientation-dependent water mobility in these tissues. The next most complex model of diffusion that can describe anisotropic diffusion is to replace the scalar diffusion coefficient with a symmetric effective or apparent diffusion tensor of water, D. 12 which could lead to additional attenuation of the NMR signal.…”
Section: Characterizing Diffusion In Biological Systemsmentioning
confidence: 99%
“…[48][49][50][51] In isolated nerves it has been shown that the magnetization decay curve, measured by the pulsed gradient spin echo (PGSE) sequence, is resolved into two or more exponentials, 51,52 each representing a different water population. The 2 H DQF technique is unique and enables measurement of the diffusion of water in each nerve compartment independently.…”
Section: Na In Biological Tissuesmentioning
confidence: 99%